The impact of Information and Communication Technology on the Financial Performance in Private Commercial Banks in Syria (Journal of Hama University, 2020)
The aim of this research is to study the impact of Information and Communication Technology on financial performance in private commercial banks in Syria. To achieve this, a sample of (7) banks was used during the period 2010-2017. The study data were collected through the annual financial reports of banks during The Period, the Panel Data method was used, the data were analyzed and tests were performed  using E-views 9.5.The most important results of research that the amount invested in the devices dont affect the rate of return on assets (ROA) and the debt rate, while the amount invested in the programs affect the rate of return on assets (ROA) and doesn't affect aff the debt rate, and the efficiency of the use of ICT affects on the return on assets and the debt rate.